Visualizing Divergence: Rhetorical Education and Historical Imagination in China and Korea (ca. 1314–1644). - Yin, Shoufu (Korean Studies, 2023)
This essay explores how basic computer programming and data visualization provides new tools to understand the respective development of rhetorical education and historical imagination in China and Korea during the same period of the fourteenth to seventeenth centuries. Gathering data from large databases that contain thousands of collections printed in China and Korea, I show that a critical divergence emerged during the mid- and late sixteenth century in the field of rhetorical training. Specifically, the historical interests of Chinese elites gravitated toward the most recent episodes in the history of their own dynasty, while Chosŏn elites were increasingly devoted to the earliest phase of the Central Civilization. These observations complement existing studies that have focused on connections between China and Korea, and offer a starting point for understanding parallels and divergences between different regions and realms in East Asia.